Monoclonal antibodies specific for H-2K and H-2D antigens on cytotoxic T cells can inhibit their function. - O'Neill, H C (1986)
Antibodies specific for murine major histocompatibility gene complex (MHC) class I H-2K and H-2D molecules present on cytotoxic T (Tc) cells have been shown to inhibit their function of target cell lysis. This could only be demonstrated by using a more sensitive assay for T-cell-mediated lysis, and many monoclonal antibodies of different Ig class, origin, and specificity can be shown to inhibit alloreactive as well as MHC-restricted Tc cells. These antibodies inhibit different activated T-cell populations to varying extents, and anti-H-2K but not anti-H-2D antibodies show a synergistic effect with anti-Lyt-2 antibodies. Data here suggest that MHC molecules may be located in or near the T-cell receptor complex on these cells.